Preparation of nanocrystalline LiNbO3 by citrate gel method - Navale, SC; Samuel, V; Ravi, V (Materials Letters, 2005)
A gel was formed when an aqueous solution of Li(NO3) NbF5 and citric acid in stoichiometric ratio is heated in a water bath at 100 degrees C. This gel on decomposition at 700 degrees C produced the fine crystallites of ternary oxide, LiNbO3 (LN). The phase contents and lattice parameters were studied by the powder X-ray diffraction (XRD). Particle size and morphology was studied by transmission electron spectroscopy (TEM). (c) 2005 Elsevier B.V. All rights reserved.
Keywords: Ceramics; Electron microscopy; electronic materials; lithium niobate; X-ray diffraction